PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNINGTIPECOURSE REVIEW HORAY BERBANTU MEDIA VIDEOPEMBELAJARAN TERHADAP HASIL BELAJAREKONOMI SISWA KELAS XI - Muhammad Rifa’i; Ningrum Ningrum (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Learning is a process of interaction of learners with educators and learning resources in a learning environment. To achieve the purpose of learning it is necessary election or use of learning models in accordance with the material that will be taught so that the expectations of the material delivered using the selected learning model can cause positive effects for learners. The purpose of this study is